2021
DOI: 10.2147/idr.s341331
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Seven General Cytokines in Acute Brucellosis Before and After Treatment

Abstract: Purpose Human brucellosis is the most common bacterial zoonosis globally that poses a severe health threat. Despite the availability of antibiotic therapy for human brucellosis, its tendencies of chronicity and persistence may lead to severe debilitating and disabling conditions in patients. Comprehensive understanding of the immune response in brucellosis will be helpful in improving the treatment strategies. In this study, we measured serum levels of T helper cell type 1 (Th1), Th2, and Th17 cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Our study revealed that the serum concentrations of TNF-α and IL-6 or IFN-γ and IL-10 in B. abortus-infected mice receiving 3-AT were notably reduced compared to those of the infected group without 3-AT treatment, yet they were still higher than the levels observed in the non-infected group. These results are consistent with the cytokine profiles observed in human brucellosis [41][42][43].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study revealed that the serum concentrations of TNF-α and IL-6 or IFN-γ and IL-10 in B. abortus-infected mice receiving 3-AT were notably reduced compared to those of the infected group without 3-AT treatment, yet they were still higher than the levels observed in the non-infected group. These results are consistent with the cytokine profiles observed in human brucellosis [41][42][43].…”
Section: Discussionsupporting
confidence: 91%
“…The cytokine levels and the CD4 + /CD8 + ratio pattern can serve as indicators of the immune status in brucellosis. In the acute phase of brucellosis, infected patients exhibit higher levels of cytokines, such as TNF-α, IL-6 or IFN-γ, and IL-10, compared to Brucella-negative individuals [41][42][43][44]. In the convalescent stage, these cytokines are reduced compared to pre-treated patients but remain elevated compared to healthy cases [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the mean of anti Brucella IgG antibodies concentration in Brucellosis patients was significantly higher than the control group, which was matched with (Guzmán-Bracho, et al, 2020) who reported that in the stage of chronic infection with Brucella, the immune system is occupied with the production of antibodies and defense cells, especially since there is no effective treatment that kills this bacteria that is transmitted through animals by drinking unsterilized milk, there will be a high rise and strong reaction of the immune system constantly [17]. The mean of IL-10 concentration in Brucellosis patients was significantly higher compared to the control group, a result that was matched with (Tang, et al, 2021) who confirmed that in acute brucellosis, the levels of IL-2, IL-10 & IFN-γ are significantly elevated in comparison with the healthy individuals [18]. Also, the mean of IL-1B concentration in Brucellosis patients was significantly higher than the control group.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, genetic associative studies identified single nucleotide polymorphisms linked to brucellosis susceptibility in the TGFB gene [ 153 , 154 ]. IL-10, another cytokine well-known for its ability to inhibit the development of Th1 type responses [ 155 ], is also induced during B. abortus infection in the mouse model [ 140 , 156 , 157 ] and increased in serum from acute and chronic patients [ 158 , 159 ]. IL-10 −/− mice produce higher levels of IFN-γ and better eliminate B. abortus than WT animals [ 160 ]; in addition, by modulating macrophage functions, IL-10 contributes to create an environment that allows enhanced bacterial survival and persistent infection [ 161 ].…”
Section: Limiting Host Immunity To Establish Chronic Brucel...mentioning
confidence: 99%